Moringa olifeira Lam. Stimulates Activation of the Insulin-Dependent Akt Pathway. Antidiabetic Effect in a Diet-Induced Obesity (DIO) Mouse Model - ATTAKPA, S. EUGÈNE; Sangaré, Machioud; BEHANZIN, G. Justin; Atègbo, Jean-Marc; Seri, Bialli; Khan, Naim (My University, 2017)
We investigated the antidiabetic effect of Moringa olifeira Lam. in a diet-induced obesity (DIO) mouse model. Six mice were randomly selected as normal controls. Moringa olifeira Lam. leaf extract at a dose of 200, 400 or 600 mg/kg body weight, glibenclamide (Glib) at the dose of 10 mg/kg (positive control) and distilled water at 10 ml/kg (control group) were administered orally by gastric intubation, and each group consisted of six mice. Insulinsensitive tissues (liver, skeletal muscle) were collected to investigate antidiabetic effects and examine the plant’s molecular mechanisms. Moringa olifeira Lam. leaf extract prevented weight gain. It also reduced blood glucose in DIO mice. Glib and Moringa olifeira Lam. leaf extract, 400 mg/kg, treatments restored insulin levels towards normal values (P < 0.05 versus diabetic control group). Western immunoblot analysis of different tissues, collected at the end of the study, demonstrated that Moringa olifeira Lam. stimulated activation of the insulin-dependent Akt pathway and increased the protein content of Glut 4 in skeletal muscle. The improvement of hepatic steatosis observed in DIO-treated mice was associated with a decrease in the hepatic content of SREBP-1, a transcription factor involved in de novo lipogenesis. The hepatic PPARα protein content in the plant extract- treated mice remained significantly higher than those of the control group (P < 0.05). In conclusion, this study provides the first evidence for direct action of Moringa olifeira Lam. on pancreatic β-cells, enhancing glucose-stimulated insulin secretion. This correlated with hypoglycaemic effects in diabetic mice associated with restored levels of plasma insulin.
Keywords: (Moringa olifeira / insulin resistance / hyperglycaemia / hyperinsulinaemia / DIO mice / Akt / GLut4 /; SREBP-1 / PPARα)